Ideology in Media Translation: Some Theoretical Perspectives - Ouachan, Abdelmajid; Sadik , Maliki Moulay; Fadoua , El Heziti (International Journal of Linguistics and Translation Studies, 2025)
As media becomes more global and multilingual, understanding the impact of translation on news dissemination is crucial. Unlike traditional perspectives that view translation as a straightforward transfer between source and target texts, media translation operates within certain norms and practices. This article explores the role of ideology in media translation, emphasizing how translation is not merely a linguistic transfer but an ideological practice. Originating from the study of ideas, ideology has evolved to encompass frameworks of power and control, shaping how information is presented and interpreted across cultures. Through a theoretical lens, the article provides insights into the power dynamics embedded in media translation, affecting global communication and public perception. Such power dynamics shape narratives to align with specific cultural, political, or institutional agendas. Additionally, by analyzing some key theoretical insights from various scholars, the study examines the ethical dimensions of media translation. Therefore, through a synthesis of theoretical perspectives, this study challenges traditional notions of equivalence, positioning media translation as a transformative process, shaped by the interplay of ideology, power dynamics and ethics, while also offering critical insights into media literacy.